Effect of size distribution of bubble groups on average volumetric heat transfer coefficient in the process of direct contact boiling heat transfer. (October 2020) - Cai, Hechang; Liu, Fanhan; Huang, Junwei; Wu, Manman; Wang, Hua; Xu, Jianxin
Abstract: A new metric, the average width of bubbles, which can be used to assessing the dynamic evolution of bubble groups in the process of direct contact boiling heat transfer, is proposed. The average width is defined as the average of distance from the bubble's edge to the centroid. The correlation model between the change of Betti number slope and the average volumetric heat transfer coefficient is established. The results show that the average volumetric heat transfer coefficient is reduced as the Betti number slope increased. Simultaneously, the size distribution modeling in the bubble groups growth direction is obtained and constants K are obtained by double-logarithm regression equation. The experimental data shows that the average width ( y ) of bubble groups is as a function of bubble growth direction stage ( x ) (y = e b x k ). The ratio ( η ) based on average width normalized is proposed and an experimental optimization strategy to characterize the excellent heat transfer efficiency is established with η ≥ 4. The value of b has a significant positive impact on average volumetric heat transfer coefficient.